2010
DOI: 10.3109/10428191003661852
|View full text |Cite
|
Sign up to set email alerts
|

Late relapses in acute myeloid leukemia: analysis of characteristics and outcome

Abstract: Relapse after 5 years of complete remission (CR) is uncommon in acute myeloid leukemia (AML). Among 2347 patients seen between 1980 and 2008, 1366 achieved CR; 942 relapsed. Eleven (1.16% of all relapses) relapsed after a CR of >5 years. The median age was 66 years (range, 37–79). Initial therapy was cytarabine plus anthracycline in six, amsacrine-based in three, and other in two. The median CR1 duration was 81 months (range, 60–137). At relapse, the karyotype was different from the initial finding in five of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 15 publications
(16 reference statements)
1
44
0
Order By: Relevance
“…For example, median OS after late relapse was 6.4 months in 1 study [4], compared to significantly longer survival times reported by us and Medeiros and colleagues. [3] This may be related to differing rates of t-AML versus true late relapse.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…For example, median OS after late relapse was 6.4 months in 1 study [4], compared to significantly longer survival times reported by us and Medeiros and colleagues. [3] This may be related to differing rates of t-AML versus true late relapse.…”
Section: Discussionmentioning
confidence: 80%
“…[2] More recent studies defining late relapse as recurrence after 5 years have reported much lower rates of late relapse (0.8% of CR1 patients in 1 study). [3,4] Our study is unique in that we define late relapse as occurring after 3 years of CR1 and report the number of late relapses in terms of all patients in follow-up and still in CR1 at 3 years—14 of 426 (3.3%). Reporting late relapses solely in terms of all patients achieving CR1—1.1% of patients in our study—may not reflect the true rate of late relapse since many patients relapse early, die of other causes, or are lost to follow-up before 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relapse after 5 years of CR is infrequent, occurring in about 0.8% of all patients who achieved CR or 1.2% of all relapsed patients. 16) Since few patients relapse after achieving CR for more than 5 years, such patients can be considered potentially cured. However, the possibility of MS recurrence must be considered in leukemic patients.…”
Section: Discussionmentioning
confidence: 99%